New Five Year Plan 1978-83 Draft Annual Plan 1978-79 Social Welfare and Nutrition Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
The Scheme envisages establishment of a Home for Women in distress in Andaman and Nicobar Islands. The Home will provide care and shelter to such women. To start the Home 15 women will be admitted initially and the number will be increased as per need of the area. They will be provided with different types of vocational training according to their capacity and aptitude in which they would be suitable like tailoring, embroidery, cane work, bamboo work and shell work.
Andaman and Nicobar Administration